Non-invasive assessment of intracranial pressure through the eyes: current developments, limitations, and future directions - Bastani Viarsagh, Solmaz; Agar, Ashish; Lawlor, Mitchell; Fraser, Clare; Golzan, Mojtaba (Frontiers in Neurology, 2024)
Detecting and monitoring elevated intracranial pressure (ICP) is crucial in managing various neurologic and neuro-ophthalmic conditions, where early detection is essential to prevent complications such as seizures and stroke. Although traditional methods such as lumbar puncture, intraparenchymal and intraventricular cannulation, and external ventricular drainage are effective, they are invasive and carry risks of infection and brain hemorrhage. This has prompted the development of non-invasive techniques. Given that direct, non-invasive access to the brain is limited, a significant portion of research has focused on utilising the eyes, which uniquely provide direct access to their internal structure and offer a cost-effective tool for non-invasive ICP assessment. This review explores the existing non-invasive ocular techniques for assessing chronically elevated ICP. Additionally, to provide a comprehensive perspective on the current landscape, invasive techniques are also examined. The discussion extends to the limitations inherent to each technique and the prospective pathways for future advancements in the field.